Ion Exchange Properties of Irradiated and Chemically Modified Clinoptilolite Regarding to Cs+ and Sr2+ - L. Akhalbedashvili; G. Todradze; N. Kekelidze; Y. Keheyan; G. Yeritsyan; R. Gevorkyan (Хімія, фізика та технологія поверхні, 2010)
The ion exchange sorption of Cs+ and Sr2+ on clinoptilolite (CL) from deposit of Armenia in initial, modified by e- and g-irradiation, decationated with a hydrochloric acid, and cation-contained forms was studied. On the basis of received data the exchange capacity Е for Sr2+ and Cs+,distribution factor Кd, sorption factor Кs were determined. It was shown that untreated CL(Ar), decationated CL(Ar)H and Ca-containing forms are characterized by a big ion exchange activity on strontium and cesium to compare with irradiated samples and the most perspective ion exchange sorbents for these ions are CL samples modified by a chemical way.